2021
DOI: 10.48550/arxiv.2111.06619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Range correction in the weak-binding relation for unstable states

Abstract: The compositeness is defined as the weight of the hadronic molecule in the hadron wave function. We can determine the internal structure of the weak-binding system without any specific models from the compositeness. In order to estimate the compositeness of the system with a large effective range, we introduce the range correction to Weinberg's weak-binding relation by modifying the correction terms. We study the applicability of the weak-binding relations by the numerical calculation and show that the improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…namely, the larger one among R int and R eff . In fact, using the effective range model [14], we explicitly construct a system which does not follow the weak-binding relation with the correction term ( 2), but is consistent only with the improved correction term (3) [10,11]. We also show that the range correction should be introduced in the correction term, by analyzing the origin of the effective range [11].…”
Section: Range Correctionmentioning
confidence: 91%
See 2 more Smart Citations
“…namely, the larger one among R int and R eff . In fact, using the effective range model [14], we explicitly construct a system which does not follow the weak-binding relation with the correction term ( 2), but is consistent only with the improved correction term (3) [10,11]. We also show that the range correction should be introduced in the correction term, by analyzing the origin of the effective range [11].…”
Section: Range Correctionmentioning
confidence: 91%
“…According to the discussion in Refs. [10,11], we introduce the range correction in the weak-binding relation by the redefinition of the length scale R typ in the correction term as…”
Section: Range Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is numerically demonstrated that the improved weak-binding relation with Eq. ( 17) has larger applicability than the previous one [16]. The effective range model in the zero range limit is one of such examples.…”
Section: Range Correctionmentioning
confidence: 97%
“…Here we would like to focus on the finite range correction in the weak-binding relation (1), stemming from the effective range [16]. To this end, we examine the origin of the effective range in several effective field theories.…”
Section: Introductionmentioning
confidence: 99%